2014
DOI: 10.3233/bme-140977
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate vs pioglitazone: Comparative study of the anti-arthritic potencies of PPAR-alpha and PPAR-gamma agonists in rat adjuvant-induced arthritis

Abstract: BACKGROUND: Rheumatoid arthritis is characterized by synovial hyperplasia, inflammatory infiltration, cartilage destruction and juxta-articular as well as generalized bone demineralization. Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily which behave as ligand-activated transcription factors in response to endogenous fatty acids and eicosanoids or isotype selective synthetic compounds as fibrates and thiazolidinediones. Beyond their key role in lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The present work demonstrates that IL-6 level in serum of arthritic animals was highly increased. In agreement with other findings [35,40,41], administration of ROSV significantly decreased the serum IL-6 level in arthritic animals. The serum level of IL-6 was also decreased in arthritic rats treated with LFLU.…”
Section: Discussionsupporting
confidence: 93%
“…The present work demonstrates that IL-6 level in serum of arthritic animals was highly increased. In agreement with other findings [35,40,41], administration of ROSV significantly decreased the serum IL-6 level in arthritic animals. The serum level of IL-6 was also decreased in arthritic rats treated with LFLU.…”
Section: Discussionsupporting
confidence: 93%
“…Histopathological examination of joint and spleen sections strongly supported these findings. In the agreement, Koufany et al (2014) reported that fenofibrate could protect against adjuvant-induced arthritis in rats. Since MMPs are released from activated macrophages during the course of RA, leading to joint destruction and release of COMP into circulation, suppression of MMP-3 and COMP levels strongly indicates inhibition of cartilage destruction (Andersson et al 2013;Kizaki et al 2015).…”
Section: Discussionmentioning
confidence: 58%
“…Treatment with a peroxisome proliferator-activated receptor-α (PPARα) agonist had similar effects, attenuating the decrease in gastrocnemius weight and fast-twitch myofibre size, and preventing the arthritis-induced increase in atrogin-1 and MuRF1 expression in a rodent CIA model [126]. In addition to positive effects in skeletal muscle, PPAR-α also has anti-inflammatory effects and studies have determined that treatment with PPAR-α agonist resulted in reduced oedema and arthritis score in arthritic rodents [127]. However, the use of PPAR agonists are not an option due to their many side effects, including congestive heart failure, bone fractures, liver disease and myopathy [128].…”
Section: Are Current Treatment Strategies Failing?mentioning
confidence: 99%